THE PROBLEM OF BORROWINGS IN RUSSIAN LANGUAGE - Samandarova G.S (Scholar Express Journal, 2025)
The work is devoted to the study of the problem of borrowings in Russian language. The nature, classification, and reasons for the appearance of borrowings, their positive and negative influence on the language are considered. Special attention is paid to the modern stage of borrowings associated with globalization and the dominance of English. The conclusions emphasize the need to maintain a balance between language enrichment and language identity
Keywords: borrowings; Russian language; globalization